Time-dependent phenotypical changes of microglia drive alterations in hippocampal synaptic transmission in acute slices - Ferrucci, Laura; Basilico, Bernadette; Reverte, Ingrid; Pagani, Francesca; Scaringi, Giorgia; Cordella, Federica; Cortese, Barbara; De Propris, Gaia; Galeone, Andrea; Mazzarella, Letizia; Mormino, Alessandro; Garofalo, Stefano; et al. (Frontiers in Cellular Neuroscience, 2024)
It is widely acknowledged that microglia actively regulate synaptic function in the brain. Remarkably, much of our understanding regarding the role of microglia in synaptic regulation is derived from studies in acute brain slices. However, it is still uncertain to what extent the preparation and maintenance of acute slices can influence microglial function and whether microglial changes may affect synaptic transmission. In this study, we examined the impact of acute slice resting time on hippocampal CA1 microglia, by assessing morphological and functional parameters at two distinct time intervals. We report that after four hours from slicing microglia undergo morphological, functional, and transcriptional changes, including a decrease in the number of branches and in their movement speed. Furthermore, microglia acquire a reactive phenotype, characterized by increased amplitude of outward rectifying K+ currents, increased expression of the pro-inflammatory cytokine Tnf-α and altered expression of the microglial receptors Cx3cr1 and P2y12r. We also examined time-dependent changes of excitatory synaptic transmission in CA1 pyramidal neurons from acute hippocampal slices, reporting time-dependent decrease in both amplitude and frequency of postsynaptic currents (sEPSCs), along with a decrease in spine density. Noticeably, sEPSCs amplitude decrease was absent in slices prepared from PLX 5622 microglia-depleted mice, suggesting that this time-dependent effect on synaptic transmission is microglia-dependent. Our findings highlight possible causal relation between microglia phenotypic changes in the hours following slice preparation and concomitant synaptic changes, pointing to the mechanisms of acute synaptic modulation, whose understanding is crucial for unraveling microglia-neurons interplay in nature. Furthermore, they emphasize the potential issues associated with experimental time windows in ex vivo samples.